1995
DOI: 10.1007/bf00298582
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound assessment of bone in patients with primary hyperparathyroidism

Abstract: Quantitative ultrasound measurements were done in a group of 26 patients (4 males and 22 females, aged 55.4 +/- 14.2 years) with primary hyperparathyroidism, and the results were compared with bone mineral density (BMD) carried out at various skeletal sites. Speed of sound (SOS), broadband ultrasound attenuation (BUA), and stiffness were measured with the Achilles ultrasound bone densitometer (Lunar Corp., Madison, WI). Mean +/- SD values of SOS, BUA, and stiffness in patients with primary hyperparathyroidism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
4
5
1
2
Order By: Relevance
“…Before surgery, both DXA and QUS measurements were significantly reduced in patients with PHPT with respect to the control group. In agreement with previous studies [9][10][11]20], we have found a relatively greater reduction in bone mass at skeletal bone sites where cortical bone dominates, such as the forearm. This finding corresponds to histomorphometric data, which have documented a preferential involvement of cortical bone with a relative preservation of cancellous bone [3][4][5][6][7].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Before surgery, both DXA and QUS measurements were significantly reduced in patients with PHPT with respect to the control group. In agreement with previous studies [9][10][11]20], we have found a relatively greater reduction in bone mass at skeletal bone sites where cortical bone dominates, such as the forearm. This finding corresponds to histomorphometric data, which have documented a preferential involvement of cortical bone with a relative preservation of cancellous bone [3][4][5][6][7].…”
Section: Discussionsupporting
confidence: 93%
“…Yet studying patients with other metabolic bone diseases may not only provide us with information about the usefulness of QUS in these diseases, but may also help in the understanding of the process by which sound interacts with bone tissue. In our patients, QUS parameters, namely BUA, showed more alterations than reported by Minisola et al [20]. This discordance may be explained by the difference in clinical characteristics of the two study populations, our patients being on average about 7 years older.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In a recent study comparing different densitometric methods in a series of predominantly female patients with primary hyperparathyroidism, radial cortical-rich sites appeared to be more sensitive than spine or femoral DXA measurements [21]. The similarity of these results obtained in patients affected by primary hyperparathyroidism with our own data supports the hypothesis that also in uremic osteopenia the prolonged PTH excess, i.e., the secondary hyperparathyroidism, plays a major pathogenetic role.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with previous data [4,23,[26][27][28], we found a significant reduction of AD-SoS in both PHPT and OP patients with respect to healthy subjects. However, ADSoS did not differ significantly between PHPT and OP patients, suggesting that speed of sound was not influenced by the different histomorphometric pattern characterizing these two metabolic bone diseases [29].…”
Section: Discussionsupporting
confidence: 82%